ASSOCIATION OF SERUM ADIPONECTIN IN NON-DIABETIC HEALTHY YOUNG ADULT OF FIRST-DEGREE RELATION OF T2DM INDIVIDUALS - HARSHVARDHAN; BHARTI KAWATRA; HARPREET KAUR WALIA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Type 2 diabetes mellitus (T2DM) is a leading metabolic disorder, with 1st-° relation (FDR) of affected individuals exhibiting heightened risk due to genetic and environmental factors. Adiponectin is an adipocyte-derived hormone. It has a central function in regulating metabolism, insulin sensitivity, or secretion. To evaluate how adiponectin is associated in healthy, non-diabetic young adults who are FDR of patients with type 2 diabetes, further adding to our knowledge of adiponectin’s influence on diabetes susceptibility and prevention among these individuals. Methods: There were 100 healthy FDR of T2DM patients and 100 age- and sex-matched controls without a family history of diabetes. Fasting blood samples were collected for analysis of glucose, lipid profile, and serum adiponectin. During the screening period, anthropometric parameters were analyzed using a standard technique. Measurements were conducted using standard biochemical kits and statistically analyzed using Statistical Package for the Social Sciences 25. Results: In this research, no significant difference was found between group 1 and group 2 regarding age or lipid profile. FDR exhibited significantly lower adiponectin levels (4.67±1.68 μg/mL) compared to controls (8.65±1.51 μg/mL, p<0.001). Conclusion: The reduced adiponectin in FDRs suggests early metabolic alterations and supports its utility as an early biomarker for T2DM risk assessment. Monitoring adiponectin concentrations in high-risk individuals could facilitate timely interventions, especially in genetically predisposed populations.